Números e operações : as contribuições de um processo de reflexão sobre a prática docente com professoras dos 4ºs e 5ºs anos do ensino fundamental - Da Costa, Leila Pessôa (2015)
The topic of Numbers and Operations (NO) is one of the subjects wherewith most of the time is spent during the early years of Elementary School (EF). This topic is considered indispensable not only for daily living activities, but also as an instrument for the development of the logical structures of the subject. The Evaluation System of Basic Education (SAEB) through Brazil Exam (PB), applied to the 5th-year students from the EF, not only demonstrates their low proficiency in this topic, but also has guided the school practices in the development of teaching strategies. Previous knowledge in teachers' education, supported by research conducted about the teaching education and about the education of teachers (MELLO, 2000; CURI, 2004; CURI and PIRES, 2008; LIMA, 2007; GATTI et al, 2011; ANDRÉ et al, 1999; ANDRÉ, 2009; GATTI et al, 2008; BATISTA and LANNER, 2007; GUALBERTO and ALMEIDA, 2009; GATTI et al, 2010; among others) showed from different perspectives that teachers have difficulties with the teaching processes in general and, in particular, with the ones related to this topic. Several authors discuss the importance of the reflection in the process of teaching education (SCHÖN, 2000; ZEICHNER, 1993; FULLAN e HARGREAVES, 2000; PONTE, 1996; NÓVOA, 1991, FREIRE, 1986). This aspect has not been considered properly in the courses where we actuate as teachers (teaching education), reason why we proposed ourselves to make a research to investigate possible contributions to a process to reflect on their classroom practices with reference to the NO to the knowledge and to the teaching action of teachers working with the 4th and 5th grades of Elementary School. Participated in this investigation ten teachers active in these grades from two schools belonging to a municipal network of education, situated in the Northwest of Parana State. The research undertaken by us, has used of the instruments for data collection an initial and final interview, the observation of their classes and by the analysis of the used materials by teachers and students. It was also reviewed the set of documents that are part of the administrative and pedagogical records of the schools and that subsidized the development of the schoolwork. The intervention process, had as its starting point the production of the students of these teachers regarding the theme NO and occurred at different times: HAs, intervals between classes, during the development of the classroom activities and outside school schedule. Observed that: the experience of these teachers as students significantly marked the education developed by them, based on procedures rather than the understanding of the concepts underlying the developed content. The process of education of teachers developed by SEDUC demonstrates a concern focused on the improvement of the learning indices achieved in the PB, which ultimately prevents the concepts, mistakenly acquired in the teaching education, to be questioned. At the end of the investigative process, it was possible to verify that the reflective process undertaken has enabled the teachers to deepen their knowledge about the NO subject and produced changes in their practice and in their conception about the teaching processes and the learning of Mathematics. The internship in the Superior School of Education in Lisbon (ESELx) was significant to the understanding of the essential aspects for the teaching education and for the education of teachers and for the analysis of our research results.